A Layered Approach to Raising Public Awareness of Macular Degeneration in Australia - Heraghty, Julie (American Public Health Association, 2012)
Between 2007 and 2011, the Australian Macular Degeneration Foundation conducted a multifaceted campaign to increase public awareness of macular degeneration. Regular national polls conducted by an independent social research company have shown that awareness of macular degeneration increased from 47% to 80% in Australians aged 16 years or older and from 58% to 92% in those aged 50 years or older. The percentage of people aged 50 years or older who reported having had their macula checked in the 2 years prior to the survey increased from 33% to 70% from 2007 to 2011. Other measures, including analysis of Medicare data, have confirmed the success of the campaign.